Analyzing the Effect of Telemedicine on Domains of Quality Through Facilitators and Barriers to Adoption: Systematic Review - Clemens Scott Kruse; Annamaria Molina-Nava; Yajur Kapoor; Courtney Anerobi; Harshita Maddukuri (JMIR Publications, 2023)
BackgroundTelemedicine has a long history; however, its efficacy has been reported with mixed reviews. Studies have reported a wide range of quality implications when using the telemedicine modality of care. ObjectiveThis study aimed to analyze the effectiveness of telemedicine through 6 domains of quality through an analysis of randomized controlled trials (RCTs) published in the literature published, to date, in 2022. MethodsA total of 4 databases were searched using a standard Boolean string. The 882,420 results were reduced to 33 for analysis through filtering and randomization. The systematic literature review was conducted in accordance with the Kruse Protocol and reported in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses; 2020). ResultsThe Cohen κ statistic was calculated to show agreement between the reviewers (Cohen κ=0.90, strong). Medical outcomes associated with the telemedicine modality were 100% effective with a weighted average effect size of 0.21 (small effect). Many medical outcomes were positive but not statistically better than treatment as usual. RCTs have reported positive outcomes for physical and mental health, medical engagement, behavior change, increased quality of life, increased self-efficacy, increased social support, and reduced costs. All 6 domains of quality were identified in the RCTs and 4 were identified in 100% of the studies. Telemedicine is highly patient-centered because it meets digital preferences, is convenient, avoids stigma, and enables education at one's own pace. A few barriers exist to its wide adoption, such as staff training and cost, and it may not be the preferred modality for all. ConclusionsThe effectiveness of telemedicine is equal to or greater than that of traditional care across a wide spectrum of services studied in this systematic literature review. Providers should feel comfortable offering this modality of care as a standard option to patients where it makes sense to do so. Although barriers exist for wide adoption, the facilitators are all patient facing. Trial RegistrationPROSPERO CRD42022343478; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=343478